Identification of Ergastic Subtances of The Order Poales - Salbila, Syasya; Parsela, Jeli; Khairani, Cut Anisa; Tinambunan, Meineta; Sarjani, Tri Mustika (Jurnal Biologi Tropis, 2023)
Ergastic objects are one of the non-protoplasmic components besides vacuoles. Ergastic objects in protoplasts can be solid and liquid.The purpose of the study was to determine how the structure and type of ergastic substances in plants of order poales. This research method includes descriptive research that describes the type and structure of ergastic substances in plants of order poales, the parts observed are bulbs, grains, stems to fruits that contain ergasticsubstances.Based on the results of research on the order of poales found that the order of poales has a diverse type of solid ergastics, such as amylum (starch) found in teapot grass plants (Cyperus rotundus), rice (Oryza sativa) and corn (Zea mays) with various shapes and types, there are also types of ergastic substances in the form of ca-oxalate crystals found in pineapple plants (Ananas comusus) and types of sugar-shaped egastic substances in sugar cane plants (Saccharum officinarum Linn).